Application Of The Project Based Learning (PjBL) Model Assisted By Augmented Reality To Increase Student Creativity On Solar System Material - Adriani, Risma; Safriana, Safriana; Ginting, Fajrul Wahdi; Muliani, Muliani; Widya, Widya (Universitas Islam Negeri Ar-Raniry, 2025)
This study examines the impact of the Project-Based Learning (PjBL) model assisted by Augmented Reality on student creativity in the solar system material at SMP Negeri 5 Lhokseumawe. Using a Nonequivalent Control Group Design, the study involved two groups: a control class (Direct Instruction with Augmented Reality) and an experimental class (PjBL with Augmented Reality), each with 20 students. Data was collected through observations, questionnaires, and multiple-choice tests. Results show that the experimental class had a significantly higher creativity score (71.53%, “creative”) than the control class (58.61%, “moderately creative”). Student responses were very positive, with an 85.78% satisfaction rate. The N-Gain score was also higher in the experimental class (0.64) compared to the control class (0.44), both in the “medium” category. This confirms that PjBL with Augmented Reality effectively enhances student creativity.